Dietary and Fluid Non-Adherence, Self-efficiency, and Inter-Dialytic Weight among Hemodialysis Patients: Original Article - Adelia Rochma; Kusnanto Kusnanto; Suprajitno Suprajitno (Alta Dharma Publisher, 2020)
Chronic Kidney Disease needs to continue treatment. It can cause some problems for patients. This research was conducted to analyze dietary and fluid non-adherence, Self-efficacy, and IDWG among patients Undergoing hemodialysis. The method used in this study is descriptive with a quantitative research approach. Instruments used in this research were closed questionnaire. The average value of diet and fluid adherence in the participants is 6.18, SE value of the respondents is 65.91, the Percentage of average IDWG, the respondents, are 4.72%. Recommendation: Further research is needed on interventions that can be applied to respondents